Managing Risk Integration for Performance Orientation among Malaysian Firms - Michael, Anak Tinggi; Shaharudin, Bin Jakpar; Ng, Kim Hui (Canadian Center of Science and Education, 2019)
The study is potentially, to explore the effect of discounting for risk on performance of firms listed in Malaysian stocks’ market. Risk management has been part of the corporate philosophy in maximizing shareholders’ wealth and firms’ profit. Managing risk cannot be done in isolation. Too often common risks pertinent to operation, liquidity and financing may be taken for granted by many firms. Risks exist on stand alone, but its implication may negatively severe firms’ performance if not addressed or dealt with properly. Integrating and managing risks may potentially improve the quality of business rocesses, which may orientate towards attaining firms’ performance at the corporate level. The 2007 global financial crisis has incidentally highlighted the importance of integrating and managing risk and its effect on business. Empirical evidences from the Panel Random Effect (RE) analysis of the above companies showed that the firm’s ability to manage and integrate operating, liquidity, and financial risks steer the firms towards performance orientation.